BỔ SUNG DẪN LIỆU THÀNH PHẦN LOÀI THÂN MỀM CHÂN BỤNG (GASTROPODA) TẠI ĐÁ TỐC TAN THUỘC QUẦN ĐẢO TRƯỜNG SA, VIỆT NAM - Nguyễn, Tài Tú; Hoàng, Thị Thùy Dương; B. I., Sirenko (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ADDITIONAL DATA ON GASTROPODA SPECIES COMPOSITION (MOLLUSCA: GASTROPODA) IN ALISON REEF, TRUONG SA ISLANDS, VIETNAM Gastropoda specimens were collected in three field trips from May, 2019 to October, 2021 in the salt lake in Alison Reef (đá Tốc Tan), Truong Sa Islands (Spratly Islands), Vietnam. Results have identified 60 species belonging to 42 genera, 21 families, 5 orders, 2 subclasses in the salt lake in Alison Reef, in which 59 species were identified to species, 1 species were identified to genera. Compared with the results of previous studies in Alison Reef, our research has recorded 49 new species for Alison Reef, 26 new species recorded for Truong Sa Islands (Spratly Islands). Results of research bring the total number of species of the Gastropoda in Alison Reef to 89 species, 54 genera, 22 families, 6 orders, 3 subclasses; bring the total number of species of the Gastropoda in Truong Sa Islands (Spratly Islands) to 290 species, 154 genera, 52 families, 12 orders and 5 subclasses. The gastropod molluscs in the salt lake in Alison Reef are distributed mainly on the coral reefs, dead coral rocks where there are rich foods and shelters.